Factors Influencing Labor Absorption in Small Industries in Padang - Aulia, Sazilla; Yulyanti, Sinta (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Raw Material Value, Investment Value and Production Value on labor absorption in small industries on Padang. This study uses a quantitative approach. The data used is secondary data obtained from the official publication of the Statistics Indonesian Center. The data analysis method used is time series data regression using the eviews analysis tool 12. The results of the analysis show that the value of raw materials has a positive and significant effect on the absorption of small industrial workers in Padang. The value of investment has a negative and insignificant effect on the absorption of small industrial workers in Padang. Production value has a negative and significant effect on the absorption of small industrial workers in Padang. From the results of the determination test, this means that the absorption of small industrial labor in Padang can be explained by the variables of raw material value, investment value, and production value with a value of 79.79%, while the remaining 20.21% is explained by variables outside the research model.